Relationship between hemoglobin glycation index and Cushing’s syndrome: a cross-sectional study in Chinese populations - Wang, Meng; Li, Shiwei; Cui, Qianhui; Huang, Bo; Cui, Jingqiu (Frontiers in Endocrinology, 2025)
BackgroundCushing’s syndrome (CS) is a group of diseases that lead to multi-organ damage and even life-threatening conditions due to prolonged exposure of the organism to high cortisol levels. In clinical work, its screening and diagnosis process is cumbersome. In this study, we explored the relationship between hemoglobin glycation index (HGI) and Cushing’s syndrome in the hope of assisting in the screening of the disease.MethodsThis cross-sectional study included 344 hospitalized patients. Subjects were analyzed by collecting post-admission laboratory indicators. Binary logistic regression analysis was used to test the correlation between HGI and CS. All patients diagnosed with CS underwent a standardized diagnostic process.ResultsOut of the total participants, 33 (9.6%) were diagnosed with CS. In the unadjusted model, the likelihood of subjects developing CS increased with increasing HGI (odds ratio: 1.59, 95% confidence interval: 1.11-2.30; P<0.05). In the fully adjusted model, the risk of CS increased by 265% for each standard deviation increase in HGI (95% confidence interval: 1.26-5.57; P<0.05). Based on receiver operating characteristic (ROC) curve analysis and Youden’s index, the sensitivity and specificity of HGI for predicting CS were 75.8% and 55%, respectively (cutoff value: -0.1185; area under the curve: 0.664; P = 0.002).ConclusionsHigher levels of HGI are associated with the risk of developing CS and contribute to screening for CS.